Efektivitas Kegiatan Cultural Exchange antara Mahasiswa Unimus Indonesia dan Mahasiswa Rajamangala Thailand dalam Memahami Keberagaman Budaya - Paramitha Maylina Afifah; Nurhayati Nurhayati; Edy Purwanto; Firdaus Firdaus (Jurnal PKM Manajemen Bisnis, 2026)
Cultural exchange activities serve as an important means of enhancing cross-cultural understanding in the era of globalization. The cultural exchange program between students from Universitas Muhammadiyah Semarang (UNIMUS) in Indonesia and students from Rajamangala University of Technology in Thailand aims to strengthen understanding of cultural diversity, promote tolerance, and foster international communication among students. The activities were conducted through cultural seminars, group discussions, traditional art performances, educational visits, and direct social interactions between participants from both countries. The program was evaluated using a qualitative descriptive approach through observation, interviews, and documentation of activities. The results indicate that cultural exchange effectively enhances participants’ understanding of cultural values, social customs, languages, and communication patterns in Indonesian and Thai societies. Furthermore, this activity also fostered attitudes of tolerance, cooperation, and mutual respect among participants. The cultural exchange program proved effective in broadening students’ international perspectives while strengthening academic ties between universities. It is hoped that this activity can be further developed as a means of strengthening multicultural education within the university environment.